Chilodonella uncinata is Not Pathogenic to Culex pipiens Mosquitoes. (15th February 2013) - Spring, Kevin J.; Zufall, Rebecca A.
Abstract: Chilodonella uncinata was previously reported to be pathogenic to Culex and other mosquitoes based on the observation of high densities of ciliates inside of dead mosquito larvae. Here, we tested whether co‐culturing Cx. pipiens with Ch. uncinata resulted in decreased survival of the mosquito larvae. We find no evidence that Ch. uncinata is pathogenic to Cx. pipiens . We suggest that Ch. uncinata may instead feed on already deceased larvae.